The Impact of School Debates on Pupils' English-Speaking Proficiency in Selected Primary Schools in Nyakabande Sub-County Kisoro District. - Nizeyimana, Muhwehwe George (Kabale University, 2024)
The purpose of this study was to establish the impact of school debates on pupils' English-speaking proficiency in selected schools of Nyakabande sub-county, Kisoro District. The study was guided by the following specific objectives; To find out whether the occurrence of school debates improves pupils' English speaking proficiency, To analyze the significance of school debates on pupils' English speaking, and to suggest the possible measures that can be put in place to promote school debates and pupils' English speaking proficiency. The study used cross-sectional surveys. The researcher used 50 respondents who were selected from primary schools which are; Gisorora Primary School and Kisoro Parents Pre & Primary School. 35 pupils 13 teachers and 2 head teachers were used and represented the whole study population. The research tools that were used to collect data include Questionnaires, interviews, and group discussions targeting the following recipients, key informants, and focused groups, and these were used to obtain both qualitative and quantitative data. The findings that the use of Vocabulary during debates improves English proficiency. Debates help learners learn more about a subject, improving listening skills and communication skills. This accounted for 8(16%) of the respondents revealed that debates. Debating can help you become a master at explaining several topics. 5(10%) suggested that Keeping Track of Time. Debate can help learners build confidence and develop language fluency and academic study skills which is not only speaking but also reading, writing listening, and research skills.